When Caregiving Ends: The Experiences of Former Family Caregivers of People With Dementia. (7th January 2017) - Corey, Kristin L; McCurry, Mary K
Abstract: Purpose of the Study: Numerous adverse physiological and psychological effects of family caregiving are documented in the literature. However, there is little knowledge about family caregivers after caregiving ends. The purpose of this study is to examine the health of former family caregivers and describe their experiences following the death of a care recipient with dementia. Methods: Eight former family caregivers were recruited using convenience sampling. Each caregiver participated in one semi-structured interview ranging from 45 minutes to 3 hours in length. The interviews were audio recorded and transcribed for qualitative content analysis. Results: Three overarching themes emerged from the data: (a) sleep disturbances, (b) changes in health status, and (c) learning to live again. Despite relief from caregiving duties, sleep disturbances in former family caregivers persisted for as long as 10 years post-caregiving. Caregivers reported changes in health such as acute health crises, ongoing illness, or a cascade of nonacute illnesses. Caregivers illustrated post-caregiving as a process of learning to live again, characterized by initial uncertainty about how to proceed in life and a reluctance to relinquish caregiving after years of identifying with the caregiver role. Implications: The results of this study suggest that there may be long-term effects of caregiving on health that persist well beyond the first year post-caregiving. Former caregivers would benefit from further research on the physical and psychological health of former caregivers after the first year of post-caregiving, the role of triggering events during post-caregiving, and interventions to meet the needs of former caregivers.